Analisis Pengaruh Net Profit Margin (NPM) dan Struktur Aktiva terhadap Struktur Modal pada PT. Krakatau Steel (Persero) Tbk - Dwi Kurniasih; Nafisah Nurulrahmatia; Aris Mundar (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to analyze the influence of Net Profit Margin (NPM) and Asset Structure on Capital Structure at PT. Krakatau Steel (Persero) Tbk. The data used is PT's annual financial data. Krakatau Steel (Persero) Tbk from year X to year Y. The analytical method used is multiple linear regression to test the relationship between the independent variables (Net Profit Margin and Asset Structure) and the dependent variable (Capital Structure). It is hoped that the results of this research will provide a better understanding of the factors that influence a company's capital structure.